BEBERAPA FAKTOR YANG MEMPENGARUHI KONTRIBUSI PENGAMBILAN KEPUTUSAN DI RUMAH TANGGA (KASUS PNS PEREMPUAN YANG MENIKAH DI KABUPATEN TABANAN) - Lestari, Ni Putu Sri Eka; Sudirman, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.04.TAHUN 2018DO - 10.24843/EEB.2018.v07.i04.p04, 2018)
This study aims to analyze, 1) the contribution of decision making in the household of married civil servants in Tabanan District, 2) the influence of wife education, husband education, age, time allocation, and position to the income of married female civil servant wife in Tabanan District , 3) the influence of wife's education, husband's education, age, time allocation, position and income of wife to contribution of decision of married woman civil servant in Tabanan regency; and 4) wife income in mediating wife's education influence, husband's education, age, and positions on the contribution of civil servant marriage decision making in Tabanan regency.                 The result of the research shows that wife education, age, time allocation, and position have positive and significant effect to income of married female civil servant wife in Tabanan regency. The husband education variable has a negative and insignificant effect on the income of female civil servant wife who has been married in Tabanan regency. Wives income mediates the influence of wife's education, age, time allocation and position on contribution of decision making of married woman civil servant in Tabanan regency. The income variable of the wife does not mediate the influence of husband education on the contribution of decision making of married women civil servants in Tabanan regency.